POCZĄTKI EKONOMII AKADEMICKIEJ W EUROPIE - Bochenek, Mirosław (Wydział Prawa i Administracji UAM, 2002)
Adam Smith’s scientific system of economics was announced in 1776. On that occasion no university faculty was created and Smith was not offered the chair of political economics professor. The first economics faculties were opened already before 1776 at German, Austrian, and Italian universities. The first economics professor was S. P. Gasser at the University of Halle, who was then followed by: J. C. Dithmar from the University of Frankfurt on the Oder, J. H. G. von Justi from Theresanium in Vienna, A. Genovesi from the University of Naples, and J. von Sonnenfels at the University of Vienna. After 1776 economics faculties were created at universities in such countries as Poland, Engand, France, and Sweden. In Poland Sz. Malewski was the first political economics professor in Vilnus, D. Krysińaki in Warsaw, J. A. Dunajewski in Lvov, and M. Bochenek in Krakow; in England T. R. Malthus in Haileybuiy was the first political economics professor, in Oxford N. W. Senior, in London J. R. McCulloch, while in Cambridge G. Pryme; in France the first economics faculty was created especially for J. B. Say, and in Sweden D. Davidson was in charge of the first economics faculty.
BEGINNINGS OF ACADEMIC ECONOMICS IN EUROPE